The equipment that were bought from the manufacturer would have the data of reliability for example, MTTF (Mean Time To Failure), MTBF (Mean Time Between Failure) or MTTR (Mean Time To Repair), however these data only valid if the operation and maintenance condition are same with the operation and maintenance condition that were given by the manufacturer. If these condition could not be satisfied by the user then the data of MTTF, MTBF and MTTR that given by manufacturer could not be able as a r - M Yamin; Kusmayanto Kadium; Hermawan Kresno Dipoyono (PERTETA, 1998)
The equipment that were bought from the manufacturer would have the data of reliability for example, MTTF (Mean Time To Failure), MTBF (Mean Time Between Failure) or MTTR (Mean Time To Repair), however these data only valid if the operation and maintenance condition are same with the operation and maintenance condition that were given by the manufacturer. If these condition could not be satisfied by the user then the data of MTTF, MTBF and MTTR that given by manufacturer could not be able as a refwence data of reliability. This research aimed to devt?loped the statistical method of probability density fimtion which can be used on the data processing which are collected during operation and maintenance of the paper machine P. T Kertas Padalarang from 1980 to 1995. By processing these data, MTTF, MTBF or MTTR of the components can be determined. To calculate the tofal failure probability of paper machine, the author used the sofrware of DFT (Diagram Fault Tree Analysis) that developed by Suryadh.na.N.N.'71 The result of this research is the total failure probability of paper machine is 0.999 at the operation time of 2000 hr. It is mean that at that operation time the machine has reached failure condition, may be it will stop suddenly. At that operation time, the reliability of machine is 0.001. The Operation time of 2000 hr could be able as a reference value for doing maintenance and repair.